Pemanfaatan E-Commerce dan Social Commerce untuk Siswa/Siswi SMK Ma’arif NU Kajen Kabupaten Pekalongan - Rahmadiane, Ghea Dwi; Alfian, Mohammad; Firmansyah, Muchammad Sofyan (Universitas Nusantara PGRI Kediri, 2020)
The phenomenon of the use of e-commerce on this smartphone or better known as m-commerce has begun to increase towards social commerce where social commerce is one of the terms that people often use to describe online shop models that utilize social media to promote products, such as Facebook, Twitter, Instagram and many more. The purpose of community service activities include empowering SMK students as the next generation of young people through the use of e-commerce and social commerce, fostering awareness of the younger generation and the people of Pekalongan Regency on the importance of using e-commerce and social commerce in improving the quality of life of the community, and introducing the existence of the Bachelor of Applied Public Accounting Program in the Polytechnic of Harapan Bersama Tegal who care and have social responsibility towards the condition of the community, especially students of Ma'arif NU Kajen Vocational School in Pekalongan Regency in the Tri Dharma of Higher Education. E-commerce is a term that is often used or heard today related to the internet, where no one knows the meaning of e-commerce clearly. Social commerce is a new phenomenon in the world of e-commerce. The method or method used in conducting community service activities is first by using a survey method, where the team conducts surveys directly to the location for initial data collection. This community service activity was held on Friday and Saturday, 22 to 23 November 2019 from 08.00-12.00 WIB and was attended by 35 students of Ma'arif NU Kajen Vocational School, Pekalongan Regency. This activity was carried out in the form of exposure to the use of e-commerce and social commerce in students of Ma'arif NU Kajen Vocational School, Pekalongan Regency, as well as training in the form of making e-commerce and social commerce online store accounts with the use of smartphones on students of SMK Ma 'arif NU Kajen of Pekalongan Regency. The following details the PKM activities and schedule.